2008
DOI: 10.1172/jci37216
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing endogenous miR-181a to segregate transgenic antigen receptor expression in developing versus post-thymic T cells in murine hematopoietic chimeras

Abstract: MicroRNAs (miRNAs) are small, noncoding RNAs that regulate gene expression by targeting complementary sequences, referred to as miRNA recognition elements (MREs), typically located in the 3′ untranslated region of mRNAs. miR-181a is highly expressed in developing thymocytes and markedly downregulated in post-thymic T cells. We investigated whether endogenous miR-181a can be harnessed to segregate expression of chimeric antigen receptors (CARs) and TCRs between developing and mature T cells. Lentiviral-encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 52 publications
(76 reference statements)
2
51
0
Order By: Relevance
“…Overlapping PCR was used to generate bicistronic expression cassettes encoding vexGFP, mCitrine, mCherry, and mCerulean linked by a P2A peptide preceded by a Gly-Ser-Gly linker (35) to the cDNAs of human Oct4, Sox2, Klf4 and c-Myc, respectively, which were cloned in a lentiviral vector under the transcriptional control of the human phosphoglycerate kinase (hPGK) promoter. Vector supernatants were produced as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…Overlapping PCR was used to generate bicistronic expression cassettes encoding vexGFP, mCitrine, mCherry, and mCerulean linked by a P2A peptide preceded by a Gly-Ser-Gly linker (35) to the cDNAs of human Oct4, Sox2, Klf4 and c-Myc, respectively, which were cloned in a lentiviral vector under the transcriptional control of the human phosphoglycerate kinase (hPGK) promoter. Vector supernatants were produced as previously described (36).…”
Section: Methodsmentioning
confidence: 99%
“…In both cases, the aim was to prevent the expression of the foreign gene by antigen-presenting cells 126,127 to avoid activation of specific lymphocyte responses to transgene products. In a similar approach, Papapetrou et al 128 demonstrated specific expression of foreign genes only in post-thymic naive or activated T cells by incorporating mirR-181a target sequence (expressed in developing T cells) in the therapeutic vector. Recently the Naldini's group 129 has demonstrated that this strategy can be used to tolerize rodents to a lentiviral-encoded antigen.…”
Section: Box 2 Tissue-specific Vs Physiologically Regulated Vectorsmentioning
confidence: 99%
“…Several miR-181 targets were inserted in the LV that encodes tumor antigen receptors. 199 This miRNA is expressed in developing thymocytes, but its expression ceases in mature thymocytes. This property was used to restrict the LV to developing thymocytes in mice upon re-engraftment with modified bone-marrow cells.…”
Section: Controlled Transgene Expression Via Mirnasmentioning
confidence: 99%